The Psychological contract in human resource management: Fostering healthy workplace relationships and emotions (Gestión y Gerencia, 2026)
The psychological contract is a key component of contemporary HR management, as it encompasses individual beliefs about reciprocal obligations between employers and employees. This study has three aims: (a) to review the evolution and current challenges of the psychological contract; (b) to examine how its fulfilment and breach affect mental health, motivation, engagement, and talent retention; and (c) to integrate the notion of “healthy sensations”—safety, belonging, recognition, and appreciation—as qualitative indicators to enrich organizational climate assessment. A qualitative approach and documentary design were adopted, with a selective review of literature (1960–2025) and relevant regulations, plus an interdisciplinary thematic analysis across psychological, sociological, regulatory (Chile), cultural, and technological dimensions.Findings indicate that fulfilment is associated with greater trust, engagement, and retention; that organizational justice and coherence between discourse and practice shape affective and behavioral responses; and that breach raises turnover intention and undermines cooperation. Based on this analysis, it is proposed to strengthen organizational awareness of employees’ individual needs and realities by incorporating qualitative and quantitative indicators that recognize personal perceptions as essential variables in building an emotional capital management model. This approach could contribute to greater humanization and proactivity in HR strategic and operational decision-making, fostering well-being, sustainable improvements in the work environment, and enhanced organizational outcomes.
Keywords: well-being; organizational climate; psychological contract; human resource management; labor relations